The Timber Floor Seismic Design by Means Finite Element Method - Abdoullah Namdar; Shan Saimai (Salehan Institute of Higher Education, 2019)
To improve accuracy results of numerical analysis, the finite element method software needs to use appropriately with considering accurate input data. Among several factors in realistic and economical seismic structural design, the damping ratio needs to be investigated as a calculated and input data in numerical analysis. In the present study, the effect of accurate damping ratio on timber floor seismic design has numerically been examined. The 6 first modes from a series of eigenvalues were selected to calculate natural frequency and damping ratio. The seismic results with and without applied calculated damping ratio were compared. The strain, displacement, and seismic load response are interpreted. The numerical analysis results were showed that the higher nonlinear displacement occurs in timber floor when the damping ratio was modified in numerical modeling. It was found that the floor seismic design is more critical compared to a column in select accurate damping ratio. The damping ratio has highly effect on timber floor seismic design.